Analisis Pengaruh Sosial Media Marketing Tiktok Terhadap Keputusan Pembelian Produk Fashion Lokal - Melisa Anzelina Simanjuntak; Restu Aji Kinanti; Gina Rivera Helandy Putri; Winda Sianturi; Mila Destasari (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This research aims to analyze the influence of social media marketing through the TikTok application on purchasing decisions for local fashion products. Digital transformation has reshaped marketing strategies into more intensive efforts through creative content and direct interaction, with TikTok serving as a primary platform to reach a broad and engaged target audience. The research method employs a descriptive quantitative approach, with data collected via online questionnaires distributed to 100 respondents using accidental sampling. The results indicate that social media marketing variables simultaneously have a significant effect on purchasing decisions, with an F-count of 452.365 (F-table = 3.94) and a significance level of < 0.001. Partially, social media marketing strategy also shows a positive and significant influence with a t-count of 21.269 and a regression coefficient of 0.850. The implication of this study highlights the importance of continuous creativity for local fashion entrepreneurs in developing digital content, as every improvement in social media appeal directly impacts the volume of consumer purchasing decisions.